Analysis Of Government Goods/Services Procurement Services At Regional Implementation Unit Iv, Bureau Of Procurement And State Property Management Services (BLPPBMN), Ministry Of Transportation - Wiratama, I Nyoman Adi; Sudiarkajaya, I Made; Kurniawan , I Gde Surya (Journal Of Social Science (JoSS), 2025)
This study aims to analyze the public procurement services at the Regional Implementing Unit IV of the Bureau of Procurement Services and State-Owned Goods Management (BLPPBMN) under the Ministry of Transportation, focusing on service quality, efficiency, transparency, and user satisfaction. A qualitative descriptive method with a case study approach was used. The findings indicate that while the e-procurement system has been implemented to enhance efficiency and transparency, several challenges remain, including process delays, technical issues, and limited personnel competence. The quality of service is considered adequate but still needs improvement, particularly in responsiveness and communication clarity. Key factors influencing procurement effectiveness include personnel competence, proper planning, and active participation from service providers. The study recommends strengthening human resource training, optimizing the electronic system, and improving supervision and accountability at all stages of the procurement process. The results are expected to contribute to enhancing procurement systems at BLPPBMN and other related government institutions.